Sharpshooter / 2. - Lynch, Chris, 1962- (Vietnam, 2012)
"Some things are worth fighting for. Of all his friends, Ivan is the only one looking forward to war. That's because Ivan has never backed down from a fight--especially when it comes to fighting for what's right. He has protected his friends from bullies for years. And now, as war erupts in Vietnam, Ivan wants nothing more than to fight for his country, just as his father did in World War II. Enlisting in the United States Army, Ivan is trained to be a sniper. And he's good at it. Very good. But Vietnam is not the war he was expecting. Somehow the glory and heroism of his father's war stories do not come so easily in the jungle. Now, for the first time, Ivan is forced to question what he's really fighting for. and whether it's a fight he can hope to win. "--